2021
DOI: 10.1038/s41587-021-01155-4
|View full text |Cite
|
Sign up to set email alerts
|

A humanized mouse model of chronic COVID-19

Abstract: OVID-19, caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) 1 , is a heterogenous disease with few therapeutic options. Although anti-viral immunity mediates viral clearance in mild COVID-19, robust inflammatory cytokines, decreased circulating lymphocytes and dysregulated myeloid and lymphocyte compartments characterize immunopathology in severe ). Accurate model systems are essential to evaluate promising discoveries, but most available rodent and non-human primate models do not reveal t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
126
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(141 citation statements)
references
References 103 publications
15
126
0
Order By: Relevance
“…S1K), highlighting the selective effects of combined anti-IFNAR2/Remdesivir therapy on chronic COVID-19 pathology. Consistent with the fibrosis, seen both in patients 32-36 and humanized mice 19 , alveolar self-renewal and differentiation programs were inhibited, resulting in the accumulation of pre-alveolar type 1 transitional cell state (PATS) program in pneumocytes 7,37-39 that was reversed in infected MISTRG6-hACE2 mice by anti-IFNAR2/Remdesivir combination therapy, restoring self-renewal and differentiation programs (Fig. S1L).…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…S1K), highlighting the selective effects of combined anti-IFNAR2/Remdesivir therapy on chronic COVID-19 pathology. Consistent with the fibrosis, seen both in patients 32-36 and humanized mice 19 , alveolar self-renewal and differentiation programs were inhibited, resulting in the accumulation of pre-alveolar type 1 transitional cell state (PATS) program in pneumocytes 7,37-39 that was reversed in infected MISTRG6-hACE2 mice by anti-IFNAR2/Remdesivir combination therapy, restoring self-renewal and differentiation programs (Fig. S1L).…”
Section: Resultssupporting
confidence: 70%
“…Two hallmarks of severe COVID-19 are a sustained interferon (IFN) response and viral RNA persisting for months 1-13,20,27,28 . This chronicity is recapitulated in SARS-CoV-2 infected MISTRG6-hACE2 humanized mice 19 . Copious Interleukin (IL)-1β, IL-18 and lactate dehydrogenase (LDH) correlates with COVID-19 severity in patients, suggesting a role for inflammasome activation and pyroptosis in pathology 5-7,14-18,29 .…”
Section: Introductionmentioning
confidence: 85%
“…Currently, our understanding of PASC and COVID-19 induced CAP/PF is poor and countermeasures are limited due to the wide spectrum of potential disease pathophysiologies. Recently, a chronic (30 dpi) SARS-CoV-2 infection model was reported in immunosuppressed, humanized mice characterized by persistent virus replication and chronic inflammation with fibrotic markers, typical of rare infections seen in immunosuppressed humans who cannot clear virus ( 65 ). We developed a model of long-term pulmonary sequelae of SARS-CoV-2 infection that persisted after virus clearance and was more characteristic of the general patient population.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have already shown the ability of engineered EVs to interact and bind to receptors of interest in vivo , including acetylcholine receptors in the brain 32 , tumor cells 27 , immune cell surfaces 49 , and viral receptors, including ACE2 40 . Since human ACE2 receptors are not naturally present in mice, a few transgenic mice models had been proposed 50,51 , but they are not readily accessible, and therefore, are not yet extensively used. Therefore, we established a xenograft model to study the in vivo targetability of EVs RBD to ACE2 following their systemic administration.…”
Section: Resultsmentioning
confidence: 99%